1970
DOI: 10.3329/sjps.v4i1.8861
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Gastroretentive Dosage Form of Ofloxacin

Abstract: The aim of the present investigation was to develop and evaluate gastroretentive drug delivery tablets (GRDDTs) of ofloxacin using different polymers such as HPMC K4M, HPMC K15M, Polyethylene oxide WSR 303, Carbopol 971P, Xanthan Gum in different ratios for local action in gastric region to eradicate Helicobacter pylori infection. The GRDDTs were prepared by wet granulation method and evaluated for physical characteristics such as hardness, thickness, friability, drug content and floating properties. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…it can be observed that both polymers polyethylene Oxide (PEO)(X1) and Carbopol 940 P (X2) have a significant effect on floating lag time. Moreover, the effect of the polymer Carbopol 940 P had significantnegative effect of on the floating lag times means increase Carbopol 940 amount (X2) will be accompanied by significant reduction in the floating lag times it might be due to the hydrophilic nature of Carbopol 940P produces faster medium penetration rate, and thus, shorter time for gel layer formation these findings are similar to what has been reported by [36].…”
Section: Fig 3: a Response Surface Plot Showing Effect Of Concentration Of Independent Variables On The Floating Lag Timesupporting
confidence: 82%
“…it can be observed that both polymers polyethylene Oxide (PEO)(X1) and Carbopol 940 P (X2) have a significant effect on floating lag time. Moreover, the effect of the polymer Carbopol 940 P had significantnegative effect of on the floating lag times means increase Carbopol 940 amount (X2) will be accompanied by significant reduction in the floating lag times it might be due to the hydrophilic nature of Carbopol 940P produces faster medium penetration rate, and thus, shorter time for gel layer formation these findings are similar to what has been reported by [36].…”
Section: Fig 3: a Response Surface Plot Showing Effect Of Concentration Of Independent Variables On The Floating Lag Timesupporting
confidence: 82%
“…The release studies were performed in triplicate, and the mean values were plotted versus time. Each sample was analyzed at 293nm using double beam UV -Visible Spectrophotometer against reagent blank [22].…”
Section: 8 In Vitro Drug Release Studiesmentioning
confidence: 99%
“…This type of drug delivery method would have comparatively less side effect and would eliminate the need for repeated dosages. 4 In pharmaceutical dosage, the formulation of drugs in multilayered / bi-layered tablets is a innovative approach for providing the loading dose and maintenance dose in a tablet. This design allows for the preparation of extended release with an immediate release quantity of drug in one layer and an extended release proportion in the second, thereby retaining a prolonged blood level.…”
Section: Introductionmentioning
confidence: 99%